Bioenergy potential of the main Agroindustrial Waste in the La Libertad Region, Perú 2019-2024 - Ferrer Lopez, Paul Martin; Gil Villalobos, Eduardo Alexander; Isuiza Gonzales, Diana Sheyla; Moncada Córdova, Juan Marchello; Quiroga Marcos, Kevin David; Silva Chuquipoma, Diego Honorato (LACCEI, 2025)
The objective of this research was to identify the agro-industrial waste of companies in the region, the biomass and energy potential of the waste in the department of La Libertad, the data collection covers the production of the years 2019-2024. Twenty agricultural crops are identified using a Pareto diagram and the analysis is reduced to four crops (asparagus, grapes, blueberries and avocado) that represent 80% of the waste production in the La Libertad region. In the results, biomass production was identified where Blueberry obtained a biomass of 778202 (ton/year), Asparagus 32375 (ton/year), Avocado 32873 (ton/year) and grapes 83081 (ton/year). On the other hand, the total heat energy potential for one of the crops, Blueberry, was identified as 38681 (kwh/year), for Asparagus 112928 (kwh/year), for Avocado it was 1146414 (kwh/year) and finally for grapes with a value of 897366 (kwh/year). In conclusion, the largest in producing biomass is the blueberry with a total production of 778202 (ton/year), in terms of electrical energy potential the greatest is the Avocado with 1146414 (kwh/year). It is recommended to evaluate the heat energy potential of other crops in Peru, to generate a meaningful comparison between the different crops that were analyzed.